Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes - Bouchard, Louise; Batista, Ricardo; Reaume, Michael (Université d’Ottawa et Institut du savoir Montfort, 2021)
fs-ref-orig: Bouchard, L., Batista, R. et Reaume, M. (2021). Évolution de principaux indicateurs de la santé de la population francophone et anglophone de l’Ontario : 2001-2014. Résultats de l’enquête sur la santé dans les collectivités canadiennes. Université d’Ottawa et Institut du savoir Montfort. fs-code-orig: Bouchard-2021a

Naviguer le maintien à domicile en communautés de langue officielle en situation minoritaire rurales : enjeux et pistes de solutions - Dupuis-Blanchard, Suzanne; Caissie, Julie (Reflets, 2021)
Le vieillissement de la population dans les provinces de l’Atlantique est une réalité courante en plus d’une composition géographique rurale et la présence de communautés de langue officielle en situation minoritaire (CLOSM). Les objectifs de cette étude descriptive qualitative étaient de 1) comprendre les services utilisés pour le maintien à domicile, et 2) déterminer les services nécessitant une amélioration pour l’accès en français. Vingt-six (n=26) personnes âgées ont participé à cette étude en région rurale de l’île du Prince Édouard. Les résultats témoignent des difficultés d’accès aux services pour le maintien à domicile tout en offrant des pistes de solutions pour l’améliorer. Mots-clés : Maintien à domicile, vieillissement, communautés de langue officielle en situation minoritaire, communauté rurale, services, recherche qualitative

Odds of anxiety and depression symptoms in school-aged children from official language minority communities - Dupuis, Jérémie B.; Bourque, Jimmy; El Adlouni, Salah-Eddine (Frontiers in Public Health, 2021)
Objectives: The aim of this paper is to assess the odds of suffering from anxiety or depression symptoms based on the presence of certain determinants of health for youth living in the province of New Brunswick, Canada, and in two linguistically different Official Language Minority Communities (OLMCs) in the same province. Methods: With a sample of 22,329 students from grades 7 to 12 in the province of New Brunswick, Canada, logistic regressions were performed to assess each determinant of health's effect on symptoms of anxiety and depression. Results: Some social determinants, like family support, social support and food insecurity, were identified as important determinants of mental health status regardless of linguistic group membership or community membership, while other determinants, such as alcohol use, cannabis use and natural environment, were more prominent in one OLMC than the other. Discussion: Social psychology and public health theories are used in an attempt to explain the results. Limitations and recommendations are also brought forward.

Loi sur les langues officielles et vitalité des minorités : mission impossible ou oeuvre inachevée ? - Landry, Rodrigue (Minorités linguistiques et société, 2021)
Notre article vise à déterminer les conditions nécessaires pour qu’une loi et des politiques linguistiques puissent avoir un effet réel sur la vitalité d’une minorité. L’article comprend trois parties. Premièrement, nous concluons que la Loi sur les langues officielles (LLO) a eu peu d’effet sur la vitalité des minorités de langue officielle. En deuxième partie, nous distinguons trois acteurs essentiels qui agissent sur la vitalité linguistique : la communauté d’intimité, la société civile de la minorité et l’État. De ces analyses, nous dégageons deux principes sociolinguistiques que toute législation linguistique devrait respecter si son objet est de favoriser la vitalité/revitalisation d’une minorité. Enfin, nous focalisons sur la partie VII de la LLO, la plus susceptible de favoriser la mise en oeuvre d’un aménagement linguistique planifié et global capable de respecter les deux principes sociolinguistiques, de coordonner une synergie d’action des acteurs essentiels et d’avoir un effet réel sur la vitalité des minorités. Mots-clés : Loi sur les langues officielles, vitalité ethnolinguistique, autonomie culturelle, aménagement linguistique, politiques linguistiques, droits linguistiques

Évaluation des besoins de santé et intégration à la culture francophone, anglophone et autochtone chez les enfants métis en milieu minoritaire - LeBlanc, Angèle; Roy-Charland, Annie; Paquette, Tara; Boulard Poirier, Jessica; Young, Nancy. L. (Enfance en difficulté, 2021)
Ce projet a pour objectif d’adapter et de traduire un questionnaire lié à la santé et au bien-être des enfants métis : la Mesure de la santé et du bien-être des enfants métis (MSBEM), en plus de déterminer si les enfants métis de la communauté du Grand Sudbury sont davantage intégrés à la culture autochtone, francophone ou anglophone. Mots-clés : Métis, intégration culturelle, minorité, besoins de santé, autorapport

Being small and outnumbered: Service and sociocultural exclusion among older linguistic minorities in Finland - Nyqvist, Fredica; Björklund, Siv; Lindell, Marina; Nygård, Mikael (Linguistic Minorities and Society, 2021)
Our study aims to analyze the social exclusion of older Swedish and Finnish speakers living as linguistic minorities in bilingual municipalities in Finland, where municipal authorities are required to offer services in both languages. Data was taken from the 2016 Language Barometer Survey, measuring the quality of language services in bilingual municipalities (n=33). For the purposes of our study, we focused on 2,030 people between the ages of 60 and 84. We included four different language groups, unilingual Swedish and Finnish speakers and Finnish-Swedish bilinguals and examined two social exclusion domains: service and sociocultural exclusion. The results showed that living as a regional minority poses a greater challenge when it comes to social inclusion for the unilingual and bilingual Swedish minority, as opposed to the Finnish-speaking minority. We conclude that linguistic rights seem to be achieved in the most egalitarian way in bilingual municipalities where Swedish is the majority language. Keywords: older adults, linguistic minority, bilingual, social exclusion, Finland

Social exclusion among official language minority older adults: A rapid review of the literature in Canada, Finland and Wales - Nyqvist, Fredica; Häkkinen, Emilia; Renaud, Alexandre; Bouchard, Louise; Prys, Cynog (Journal of Cross-Cultural Gerontology, 2021)
It has been suggested that older adults from minority linguistic and ethnic communities face higher risks of being socially excluded. The aim of this review was, therefore, to explore and review social exclusion studies conducted among official language minority older adults in three countries, namely Canada, Finland and Wales. A rapid review approach was used to review scientific literature in line with six social exclusion domains. The literature searches were made in Finnish, Swedish, English, French and Welsh and were restricted to research published within the timeline of 2001 – September 2019 and yielded 42 articles. The included studies were categorized into three different domains: socioeconomic influences, social participation and societal conditions. Converging and diverging patterns of social exclusion in old age were identified between the linguistic minorities. Linguistic barriers regarding access to health care and receiving health information were common across the three linguistic contexts, whereas exclusion from social participation was noticed amongst the linguistic minorities in Canada and Wales. Some connections between belonging to a linguistic minority and being exposed to a lower socioeconomic status and higher poverty risk were made, however, these findings were not robust across all three countries. The findings indicated that experiences of exclusion could be considered fairly common among linguistic minority older adults. We conclude that the research evidence presented in the review sheds light on issues of social inequality in old age between linguistic majorities and minorities, thus identifying important aspects of social exclusion to guide future research as well as policy and practice.

Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication] - Ontario mental health & addictions virtual care collaborative (Centre for Addiction and Mental Health (CAMH), 2021)
fs-ref-orig: Ontario mental health & addictions virtual care collaborative. (2021). Active offer of mental health and addiction services: How to serve Francophones at their most vulnerable times [oral communication]. Centre for Addiction and Mental Health (CAMH). fs-code-orig: Ontario mental health & addictions virtual care collaborative-2021

Sense of belonging and social climate in an official language minority post-secondary setting - Penner, Kailey; de Moissac, Danielle; Rocque, Rhéa; Giasson, Florette; Prada, Kevin; Brochu, Paul (Canadian Journal of Higher Education, 2021)
Perceived sense of belonging and positive social climate on campus are crucial elements for post-secondary students, as they contribute to academic achievement, positive mental health, and help-seeking. Few studies have explored post-secondary students’ sense of belonging and perceptions of social climate in an official language minority campus, which attract Canadian-born francophones, anglophones who pursue higher education in their second language, and francophone international students. With declining student mental health and greater ethnolinguistic diversity of post-secondary students on Canadian campuses, this important study aims to explore francophone students’ perceived sense of belonging and social climate on campus. In total, 35 students from different ethnolinguistic backgrounds took part in focus groups or individual interviews. Domestic students with French as their first language more often reported positive social climate on campus and a sense of belonging, in contrast to international students and students with French as a second language. A common obstacle to connecting with others was language insecurity in one of the official languages, as both are currently used on campus. Universities hosting students of multiple linguistic diversities should provide courses and campus events to stimulate intercultural knowledge and dialogue.

Approach to the status and management of languages in the catalan public health care system - Pere Mas, Jordi (Linguistic Minorities and Society, 2021)
This article deals with the situation of languages in healthcare in Catalonia. It reports on the measures being carried out by the Ministry of Health of the Government of Catalonia to guarantee that the population may be attended to in their own official language, whether Catalan, Spanish or Occitan, and specifically to promote knowledge and use of Catalan among professionals working in the health system. It provides data on the migratory flows of doctors and nurses and sociolinguistic data. Other sections deal with healthcare services provided in non-official languages and in Catalan sign language, as well as language-related complaints and the measures implemented to make Catalan a suitable and prestigious language for medical and scientific communication. It concludes by listing the challenges that still need to be tackled to give Catalan greater presence and to raise its status in the field of health. Keywords: healthcare, health, Catalan, linguistic planning, healthcare professionals, official languages, Catalonia

Quebec’s English-speaking community and the partnership approach of its networks in health - Pocock, Joanne (Linguistic Minorities and Society, 2021)
This article discusses the networking and partnership approach of improving access to public health and social services, with an interest in informing best practices for official language populations in a minority context. The case of Canada’s official language minority residing in the province of Quebec and its Community Health and Social Services Network (CHSSN) is explored. Elements that support or inhibit partnership functioning, including innovative community-based participatory evaluation (CBPE) techniques, are explored. The contribution of the approach in improving the situation of Quebec’s minority language communities with respect to their health care access is highlighted. Keywords: official language minority communities, intersectoral partnerships, access to public health care, language policy, community-based participatory evaluation (CBPE)

Des nôtres : une analyse des besoins des personnes LGBTQ2S d’expression française du Manitoba - Prada, Kevin; de Moissac, Danielle; Gueye, Ndeye Rokhaya (Collectif LGBTQ du Manitoba et Université de Saint-Boniface, 2021)
Cette étude, menée sous l’impulsion du Collectif LGBTQ* du Manitoba, est la première à sonder les besoins de la communauté LGBTQ2S d’expression française au Manitoba (désormais la « Communauté »). L’objectif était de brosser le portrait de la situation actuelle de ses membres de 18 ans et plus quant à 1) leur profil sociodémographique et ethnoculturel; 2) leurs besoins en matière de soutiens sociaux et de soins de santé; 3) leurs perceptions de discrimination ou de stigmatisation, tant par rapport à la langue qu’à l’orientation sexuelle et/ou à l’identité de genre; et 4) leurs priorités pour l’avenir. Par l’entremise d’un sondage en ligne, la Communauté a su nous informer de ses besoins prioritaires, particulièrement en matière de santé mentale et de soutien social.
fs-ref-orig: Prada, K., de Moissac, D. et Gueye, N. R. (2021). Des nôtres : une analyse des besoins des personnes LGBTQ2S d’expression française du Manitoba. Collectif LGBTQ du Manitoba et Université de Saint-Boniface. fs-code-orig: Prada-2021

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Santé des francophones en milieu minoritaire. Quelle est la situation en Colombie-Britannique ? | The health of Francophone minorities. What does it mean for British Colombia? - RésoSanté Colombie-Britannique (What does it mean for British Colombia, 2021)

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Pour une réforme de la santé respectueuse des deux communautés linguistiques officielles. Mémoire présenté à l’honorable Dorothy Shephard, ministre de la Santé, dans le cadre de la consultation publique sur l’avenir des soins de santé dans la province du Nouveau-Brunswick - Société de l'Acadie du Nouveau-Brunswick (2021)

Dérives : une histoire sensible des parcours psychiatriques en Ontario français - Thifault, Marie-Claude; LeBel, Marie (Les Presses de l'Université d'Ottawa, 2021)
fs-ref-orig: Thifault, M.-C. et LeBel, M. (2021). Dérives : une histoire sensible des parcours psychiatriques en Ontario français. Les Presses de l'Université d'Ottawa. fs-code-orig: Thifault-2021

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.